Arsenic trioxide inhibits the differentiation of fibroblasts to myofibroblasts through nuclear factor erythroid 2‐like 2 (NFE2L2) protein and the Smad2/3 pathway. Issue 3 (14th October 2018) - Zhong, Lingzhi; Hao, Haojie; Chen, Deyun; Hou, Qian; Zhu, Ziying; He, Wenjun; Sun, Sujing; Sun, Mengli; Li, Meirong; Fu, Xiaobing
Abstract : Background: Tissue contraction and the extracellular matrix deposition are part of the pathogenesis of hypertrophic scars. The transcriptional factor NFE2L2 inhibits fibroblast differentiation in idiopathic pulmonary fibrosis and promotes myofibroblast dedifferentiation. Our previous study showed that the transcription factor NFE2L2 was strongly induced on treatment with arsenic trioxide (ATO). Objective: The present study sought to investigate the effect of ATO on myofibroblast formation to determine its potential role in hypertrophic scar treatment. Methods: Small interfering RNA against NFE2L2 was used on treatment with ATO in human skin myofibroblasts. The expression levels of fibrosis markers were assessed by reverse transcription polymerase chain reaction, western blot, and immunofluorescence staining. The transforming growth factor‐β1 (TGF‐β1)/Smad2/3 signaling was detected by western blot. A rabbit ear model was used to evaluate the antifibrotic role of ATO. Results: At the cellular level, ATO abolished fibroblast differentiation in response to TGF‐β1. ATO reduced TGF‐β1‐induced reactive oxygen species accumulation through increased expression of the antioxidant gene HO‐1 in fibroblasts. In addition, ATO promoted the nuclear translocation of NFE2L2 and inhibited the phosphorylation of Smad2/3. In the rabbit ear model, ATO prevented the progression of hypertrophic scar formation. Conclusions: This study provides the first evidence implying that ATO inhibits the formation of myofibroblasts in vivo and in vitro and provides a possible treatment for hypertrophic scars. Abstract : Tissue contraction and the extracellular matrix deposition are part of the pathogenesis of hypertrophic scars. The present study sought to investigate the effect of arsenic trioxide (ATO) on myofibroblast formation to determine its potential role in hypertrophic scar treatment. This study provides the first evidence implying that ATO inhibits the formation of myofibroblasts in vivo and in vitro and provides a possible treatment for hypertrophic scars.